A Case of Neuropsychiatric Systemic Lupus Erythematosus With Hair Loss as the First Diagnostic Symptom - He, Xun; Duan, Xi-Ling; Liu, Jing-Song (Frontiers in Psychiatry, 2022)
Neuropsychiatric systemic lupus erythematosus is a serious complication of systemic lupus erythematosus. A 33-year-old female patient had repeated hair loss for more than 3 years. A dermatologic examination showed several pieces of irregular shaped hair loss patterns in the center of the patient’s scalp. The systemic treatment included oral hydroxychloroquine, aspirin enteric coated tablets and prednisone, intrathecal injection of dexamethasone and methotrexate. The local treatment included intralesional injection of triamcinolone acetonide and lidocaine in lesion area, 0.1% tacrolimus ointment for external use. After 2-month treatment, the patient grew in non-scarring patchy alopecia region with no further hair loss.